PEMBERIAN BANTUAN HUKUM OLEH ADVOKAT SEBAGAI IMPLEMENTASI OFFICIUM NOBILE DALAM SISTEM PERADILAN PIDANA - Adri Indra (Unes Journal of Swara Justisia, 2019)
Act number 18 Year 2003 article (1 and 2), the advocate's profession is a person who gives legal services, both within and outside the Court meet the requirements based on the provisions of this Act. The actions of the irregularities committed by persons-persons advocate that damage the image of the profession of advocate today, should not be a barrier that stops the execution of the noble profession of advocates themselves. Starting from dotted background problems that have been described above, it can be raised two principal issues, namely: 1. How is the grant of legal aid by advocates as implementation of the officium nobile in the criminal justice system? 2. What are the obstacles found by advocates in the granting of legal aid as officium nobile in the criminal justice system to answer both of the above problems in this research is descriptive research. The approach used in this study are normative juridical approach as the main approach that is supported by empirical juridical approach. The granting of legal assistance by advocates as implementation of the officium nobile in the criminal justice system have not done well because: still found irregularities committed by advocates. Restricting factors that affect the implementation of the grant of legal aid can be divided into four factors: First the legal substance of the factors (legal substance use). the structure of the law (legal structure). the culture of the law (legal culture). The fourth.